The contributing factors of teamwork towards organizational performance at supplier quality department Perusahaan Otomobil Nasional Sdn Bhd / Arni Shuhada Suridin - Suridin, Arni Shuhada (2016)
The purpose of this study was to identify whether the factor of teamwork is contribute to the organizational performance. The selected organization was Perusahaan Otomobil Nasional Sdn. Bhd. This correlation research was to determine whether there is any relationship that exist between variables with the existence of correlation. Staff at Supplier Quality Department of Perusahaan Otomobil Nasional Sdn. Bhd. is the sampling frame while the population of 119 employees, 100 respondents have given feedback. In addition, the internal consistency using Cronbach’s Alpha are also use to verify the measurement used later in the Chapter 4. The unit of analysis is individual with instrument of Likert Scale question. Therefore, Statistical Package for Social Science (SPSS) version 22.0 to compute the correlation of the variables is used to collect data from the questionnaire. This research should make a contribution towards the relationship between teamwork factor towards organizational performance in an organization. The result of research shows that all variables are significant correlated with another thus the hypothesis were accepted and another thus the hypothesis were rejected.